Endothelin-1 axis fosters YAP-induced chemotherapy escape in ovarian cancer. (1st November 2020) - Tocci, Piera; Cianfrocca, Roberta; Sestito, Rosanna; Rosanò, Laura; Di Castro, Valeriana; Blandino, Giovanni; Bagnato, Anna
Abstract: The majority of ovarian cancer (OC) patients recur with a platinum-resistant disease. OC cells activate adaptive resistance mechanisms that are only partially described. Here we show that OC cells can adapt to chemotherapy through a positive-feedback loop that favors chemoresistance. In platinum-resistant OC cells we document that the endothelin-1 (ET-1)/endothelin A receptor axis intercepts the YAP pathway. This cross-talk occurs through the LATS/RhoA/actin-dependent pathway and contributes to prevent the chemotherapy-induced apoptosis. Mechanistically, β-arrestin1 (β-arr1) and YAP form a complex shaping TEAD-dependent transcriptional activity on the promoters of YAP target genes, including EDN1, which fuels a feed-forward signaling circuit that sustains a platinum-tolerant state. The FDA approved dual ET-1 receptor antagonist macitentan in co-therapy with cisplatin sensitizes resistant cells to the platinum-based therapy, reducing their metastatic potential. Furthermore, high ETA R/YAP gene expression signature is associated with a poor platinum-response in OC patients. Collectively, our findings identify in the networking between ET-1 and YAP pathways an escape strategy from chemotherapy. ET-1 receptor blockade interferes with such adaptive network and enhances platinum-induced apoptosis, representing a promising therapeutic opportunity to restore drug sensitivity in OC patients. Highlights: ET-1 receptor/β-arr1 upregulates YAP activity via the modulation of RhoA and actin dynamics in platinum-resistant OC cells. YAP, as β-arr1 partner, transduces the ET-1 signaling into a precise TEAD transcriptional program allowing drug resistance. The ET-1- β-arr1-YAP axis provides a positive feedback loop that fuels apoptosis evasion. Macitentan, targeting ET-1R/YAP adaptive activities, sensitizes OC cells to cisplatinum and reduces metastatic progression.